The role of the pharmacist and pharmacy assistant as opinion leaders in the decision to purchase health and beauty aid products - R. S.M. Suttner; G. E. Staude; J. Viljoen (South African Journal of Business Management, 1988)
The authors investigate opinion leadership at the retail pharmacy level with regard to the purchase of health and beauty aid products. The characteristics of opinion leaders are identified and both pharmacists and pharmacy assistants are assessed in terms of these characteristics. The proposition that both the pharmacist and the pharmacy assistant qualify as opinion leaders is confirmed using a sample of 251 white, female consumers of health and beauty aid products. The implications of this finding for both pharmacy retailers and the manufacturers/marketers of health and beauty aid products are discussed.
Keywords: 650